Recent Publications (Quarterly Journal of Economics, 1943)
Recent Publications Get access The Quarterly Journal of Economics, Volume 58, Issue 1, December 1943, Pages 153–156, https://doi.org/10.1093/qje/58.1.153 Published: 01 December 1943